1975
DOI: 10.1063/1.88483
|View full text |Cite
|
Sign up to set email alerts
|

Structural investigation of cold-rolled metallic glasses using positron annihilation methods

Abstract: The effect of cold rolling on the structure of a metallic glass Pd0.775Cu0.06Si0.165 and a crystalline Pd has been investigated using positron annihilation methods. Only slight change in both the positron lifetime and angular distribution upon cold rolling has been noted for the metallic glass. This is in strong contrast to a large change observed for the crystalline Pd. It is therefore concluded that cold rolling of the metallic glass induces no vacancylike defects. It is also suggested that the local atomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
2

Year Published

1977
1977
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 3 publications
2
15
0
2
Order By: Relevance
“…[4][5][6][7][8][9][10][11][12] The functional dependence of the disordering process on these quantities is a fortiori unknown. It seems clear, though, that the process is accompanied by shear-induced dilatation, [13][14][15][16] a phenomenon that has been known for years in the deformation of soils that consist of randomly packed grains. 17,18 One expects deformation-induced disordering to occur during homogeneous deformation as well.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12] The functional dependence of the disordering process on these quantities is a fortiori unknown. It seems clear, though, that the process is accompanied by shear-induced dilatation, [13][14][15][16] a phenomenon that has been known for years in the deformation of soils that consist of randomly packed grains. 17,18 One expects deformation-induced disordering to occur during homogeneous deformation as well.…”
Section: Introductionmentioning
confidence: 99%
“…Free volume change induced by plastic deformation has been investigated by using various techniques such as positron annihilation, 9,10) direct density measurement, 11,12) TEM and SEM observation, 2,3) fluctuation electron microscopy, 13) and so on. However, the experimental techniques have inherent limitations in spatial and temporal resolutions; and most tests have to be performed after sample failure.…”
Section: Introductionmentioning
confidence: 99%
“…73) Positron annihilation studies of deformed bulk Zr-glasses support this view. 77) By contrast, earlier work on cold-rolling of metallic glasses suggested that the rolling would cause a densification through local regrouping of atoms. 78) In a Mössbauer-study of coldrolled Fe-Ni-glasses 79) it was found that the deformation following cold rolling was not only confined to shear-bands, but distributed throughout the volume of the sample.…”
Section: Crystallization Reactions During Intense Deformationmentioning
confidence: 83%